Isothermal short-term oxidation behavior of MAR-M246 nickel-based superalloy at 800°C and 1000°C - Baldan, Renato [UNESP]; Latu-Romain, Laurence; Wouters, Yves; Chaia, Nabil; Alkmin, Luciano B.; de Sousa Malafaia, Artur M. (Wiley, 2022)
Superalloys are widely employed at high temperatures for structural applications. Hence, knowledge about the oxidation of these materials is essential. However, the literature is scanty when it comes to some families of superalloys. The purpose of this study was therefore to analyze the MAR-M246 polycrystalline alloy in isothermal short-term tests at 800°C and 1000°C for up to 240 h. Thermodynamic simulations were performed to evaluate the material's phase stability as a function of temperature and to assess the expected phases in response to oxygen pressure. The oxidized samples were characterized by SEM-EDS and DRX, which revealed a tendency for scaling of oxidized material, particularly at temperatures of 1000°C. Nevertheless, protective layers of Cr2O3 and Al2O3 oxides were formed, which enabled the formation of fairly thin oxide layers, in addition to NiO and complex oxides. The region of the metallic substrate close to the oxide layer underwent aluminum depletion, causing the gamma-prime phase to disappear, as well as formation of aluminum oxides and titanium nitrides. Last, a good correlation was found between the thermodynamic simulations and the oxides that were formed.
Keywords: high temperature materials; isothermal oxidation; MAR-M246; microstructure; superalloys